Колекція видів роду Crataegus L. у Криворізькому ботанічному саду НАН України: історія створення та сучасний стан - Yukhimenko, Yu.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
We studied creation history of collection of species of the genus Crataegus L. under the conditions of Kryvyi Rih Botanical Garden of the NAS of Ukraine. We ascertained that the most quantity of hawthorns was planted in 1980–1992 and 2009–2016, namely 70 samples with common quantity 387 examples. We presented data about contemporary taxonomical composition of introduced hawthorns: 59 species, 4 varieties, 1 cultivar. We defined basic biometrical, ecological and biological characteristics of hawthorns: height, crown diameter, levels of flowering, fruitage and life status.